Das Minas às Gerais: um estudo sobre as origens do processo de formação da rede urbana da Zona da Mata mineira - Josarlete Magalhaes Soares (2009)
The search for the origins, for the way the urban concentration of certainpopulations have worked provides valuable clues for the comprehension of the present complexity of their network of cities and inspires in those populations a feeling of identification with and appreciation of their local characteristics, allowing for new possibilities for action in relation to region planning. In that sense, the study that have subsidized the development of the present work have as aim to show the waythe occupation of the territory that presently corresponds to Zona da Mata region of the Brazilian estate of Minas Gerais have worked, having as reference the formation process of its urban nucleus. We proceeded, then, to the identification of the features of that process, and of the agents and interests involved in it, trying to shad some light that allows us to understand the present conformation of the regional urban network.In that sense, the analyses presented here have aimed to recover thehistorical process of constitution of the set of urban centers of the region, having as research timeframe the eighteenth and nineteenth centuries. The elements that served as landmarks for those agglomerations have been delineated, in order to highlight the political, economical and symbolical relationships that have established in the territory and the way that have contributed the occupation of the space. The starting point of our investigation was the forest regions adjacent to the central mining area, back in the seventeenth century. The hardships imposed by thenatural environment have affected the settlement, keeping it relatively constraint in that moment. However, the drop in the income of gold mining, associated to the expansion of subsistence agriculture, have modified that scenery, leading to a process of official openness and economical exploration of those areas. That process have been intensified in the first decades of the nineteenth century, being furtherpotentialized by the expansion of coffee plantations. From then on, the Zona da Mata urban network becomes effectively structured, resulting in the consolidation of several urban nuclei in its territory.